Winds of Change: Social Inequalities and Economic Consequences of Wind Energy in the Isthmus of Tehuantepec - García-Martínez, Amira María; Ramírez-Martínez, Silvia Olivia; López-Vázquez, Esteban; Quero-Ramírez, Guillermo; Ramírez-Salinas, Cristóbal; Narváez-Pascual, Jesús Elías; Cortés-Jiménez, Edgar Alberto; García-Jarquín, Brenda; Sánchez -Soriano, Marbella; Sarubbi -Baltazar, Fernando Adrihel; Girón-Laces, Vicelia; Jimenez-Hernandez, Aurelio (Science and Technology: Developments and Applications Vol. 9, 2025)
This study examines the socioeconomic and environmental impacts of wind energy development in the Istmo of Tehuantepec, Mexico, focusing on the municipalities of La Venta (Juchitán) and Santo Domingo Ingenio. Through a comparative analysis of census data from 2,251 households, we assess disparities in employment, land ownership, and economic benefits derived from wind farms. Key findings reveal that: (1) Santo Domingo Ingenio exhibits higher wind turbine density (1–3 turbines per household) and male-dominated employment compared to La Venta; (2) only 11.69% of La Venta’s Gross Local Product (GLP) stems from wind farms, with businesses (38.59%) and services (27.16%) dominating the local economy; and (3) land lease conflicts and marginalization persist, exacerbated by opaque negotiations and unequal benefit distribution. The study highlights how neoliberal policies and transnational investments perpetuate social inequalities, despite wind energy’s potential for regional development. We argue that equitable frameworks—centered on community participation, transparent land agreements, and local manufacturing—are critical to reconciling renewable energy goals with social justice in marginalized regions.